1991
DOI: 10.1021/j100167a024
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved monomer and excimer fluorescence of 1,3-di(1-pyrenyl)propane at different temperatures: no evidence for distributions from picosecond laser experiments with nanosecond time resolution

Abstract: Monomer and excimer fluorescence decays of 1,3-di( 1 -pyrenyl)propane (!Py(3)lPy) in «-heptane are measured at different temperatures by using time-correlated single-photon counting (SPC). The decays at 61 °C are triple-exponential with decay times and amplitudes independent of the number of total counts, excitation wavelength, and width of the excitation pulse. At -43 °C and lower temperatures, single-exponential monomer decays are obtained, next to triple-exponential excimer records. Aggregates of lPy(3)lPy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 0 publications
4
85
1
Order By: Relevance
“…It has been argued in the literature that in organic solvents close to ambient and higher temperatures 1Py(3)1Py excited-state intensity decays do not comply to a double-exponential decay model. 45 The Thistlethwaite group reported that in common organic solvents, 1Py(3)1Py time profiles of emission intensities did not fit to a double-exponential model (the Birk's scheme, Scheme 2) under ambient conditions. 50 While the monomer decay could be analyzed as a sum of two exponentials, the excimer decay did not take the form of a difference between two exponentials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued in the literature that in organic solvents close to ambient and higher temperatures 1Py(3)1Py excited-state intensity decays do not comply to a double-exponential decay model. 45 The Thistlethwaite group reported that in common organic solvents, 1Py(3)1Py time profiles of emission intensities did not fit to a double-exponential model (the Birk's scheme, Scheme 2) under ambient conditions. 50 While the monomer decay could be analyzed as a sum of two exponentials, the excimer decay did not take the form of a difference between two exponentials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While it is observed for 1,5-bis(1-pyrenylcarboxy)pentane in alkane solvents and toluene under ambient conditions, 53 for 1Py(3)1Py it is only reported at and below −43°C in heptane. 45 It is clear that a solubilizing medium constituted of PEG hinders the dissociation of intramolecular excimer formed by 1Py (3) 6 ] in the temperature range 10−90°C and PEG200, PEG400, PEG600, and in PEG1000 in the range 60−90°C were fitted to two-and three-exponential functions (extracted parameters and the corresponding best fit exponential function are reported in Tables 1 and S1). Careful examination of the data reveals that for all PEG systems in the range 60−90°C, the [I M (t)] decay better fits to a double-exponential decay model, and the fits to the triple-exponential model do not result in any meaningful improvement in reduced χ 2 values and/or other parameters.…”
Section: Articlementioning
confidence: 99%
“…Another useful probe is 1,3-bis(1-pyrenyl)propane (P3P) containing two pyrenyl moieties, which can form an intramolecular excimer as a result of conformational changes that bring the excited and non-excited chromophores together. This process is expected to be more efficient in a more fluid environment; for this reason the intensity ratio of the excimer to monomer emission maxima, I E =I M ; in the P3P fluorescence spectra can be used to estimate the local viscosity in the host [3,4]. This approach was used in recent work from our laboratories, where both P3P and P were used to examine self-assembling of ionomers in aqueous solutions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…[3] A correlation between excimer-forming probability and polymer relaxation processes was qualitatively explained on the basis of some simple excimer-formation kinetic scheme under the low-and high-temperature limit approximations. [25,27] Using this kinetic scheme, we considered in that paper: 1. The formation of sandwich complexes of Py3MPy inside the LDPE matrix was a diffusion-controlled process described at the lower temperature limit, ca.…”
Section: Systemmentioning
confidence: 99%
“…[4,5] Several of these studies concerned the excimer formation mechanism for these molecules in fluid media. Nevertheless, the mechanism of excimer formation is still controversial.…”
Section: Introductionmentioning
confidence: 99%